Comportamento motor e a participação no ambiente domiciliar de lactentes nascidos prematuros e a termo: estudo longitudinal - Fritsch, Stefani Raquel Sales (2024)
Prematurity is a biological risk factor that may affect the central nervous system. Premature infants may present delays in the acquisition and improvement of motor skills when compared to at term infants. It is estimated that 14 million preterm infants were born in 2020 worldwide. The biopsychosocial approach is paramount to the understanding of direct or indirect impacts of biological and environmental risks on child development. Due to differences in motor development trajectories between premature and at term infants, it is necessary to evaluate motor development both qualitatively and quantitatively, together with its various relevant factors. This is achievable by a combination of assessment instruments, such as the Infant Motor Profile (IMP), Affordances in the Home Environment for Motor Development – Infant Scale (AHEMD-IS) and the Young Children’s Participation and Environment Measure (YC-PEM). Objectives: Compare and identify in which domains of the Infant Motor Profile infants born prematurely may present delays in relation to at term infants and verify whether there are associations between the motor development of infants, participation and affordances present in the home environment according to the biopsychosocial model. Method: Prospective longitudinal study on a convenience sample. 72 infants, subdivided between preterm (32) and at term (35), participated in the study. Infants were monthly evaluated from their sixth to their tenth month of age, corrected if preterm. Neither infants with genetic alterations, nor only twice evaluated were included. Assessments were performed in accordance to the biopsychosocial model. Motor development was assessed by the total IMP score and of its domains: variation, performance, adaptability, symmetry and fluency. The covariates which were accounted for were participation and affordances in the home environment, personal and contextual factors. Participation was assessed by the YC-PEM, translated and adapted to the Brazilian context, considering its raw score, frequency and involvement means. Affordances were assessed by AHEMD-IS, considering total questionnaire score, physical space, variety of stimuli, gross and fine motor toys. Remaining contextual factors were sex, birthweight, head circumference at birth, jaundice at birth, maternal age, maternal marital status, maternal education, number of adults and children in the household, type of residence, whether infant attends daycare, per capita income and socioeconomic status measured by the poverty income ratio associated with maternal education. Different comparison tests were carried out, depending on data homogeneity, as well as mixed linear regression tests with p > 0.05. Results: At 7 months, preterm infants presented significantly lower adaptability score (U = 331.50; p = 0.006; moderate effect size, r = 0.34) and significantly higher fluency score (U = 366.50; p = 0.012; small effect size, r = 0.28) relative to at term infants. Factors positively associated with motor development were: higher family income (β = 0.30; p = 0.025) for the variation domain; greater variety of AHEMD-IS stimuli (β = 2.96; p = 0.014), greater family income (β = 0.45; p = 0.035) and greater maternal age (β = 0.21; p = 0.036) for the adaptability domain; house residency type (β = 3.40; p = 0.036) and larger head circumference at birth (β = 1.05; p = 0.001) for the fluency domain; house residency type (β = 3.92; p = 0.025) for the performance domain; excellent to adequate (β = 1.30; p = 0.005) and from moderately or less than adequate to excellent (β = 1.27; p = 0.005) AHEMD-IS stimuli variety, gender male (β = 1.32; p = 0.024) and higher family income (β = 0.31; p = 0.008), for the total IMP score. Age was a positive factor for all domains and the IMP total score (p < 0.0001). Conclusion: At 7 months, preterm infants presented higher scores in the adaptability domain and lower scores in the fluency domain ]when compared to at term infants. Results showed that higher monthly income, greater stimuli variety, greater maternal age, greater head circumference at birth, house residency type, being male and age are positively associated with motor development. Contributions: Information pertaining to differences between motor development trajectories of preterm and at term infants were obtained, as well as about which contextual factors are associated with motor development components. This study contributes to the understanding of consequences of prematurity and contextual factors for motor development, thereby enabling health professionals to provide better guidance to parents of infants with motor delay.